Menjadi Jemaat Publik: Menggereja Secara Misional, Relasional, dan Inkarnasional di Ruang Publik - Hariman Pattianakotta (STFT Jakarta, Indonesia, 2021)
Being church in the world is a way of life for church that is determined by its DNA and God’s design. This article offers the metaphor for a church in the world called “public congregation.” It is characterized by three dimensions—missional, relational, and incarnational. This article uses Joas Adiprasetya’s concept of perichoresis in conversation with Leonard Sweet’s thoughts on the missional, relational, and incarnational (MRI) church. The conversation is further extended to include the metaphoric approach by Donald Messer to argue for the relevance of public congregation as a metaphor for church life and orientation toward the world.